Critical role of the cholinergic system for object-in-place associative recognition memory - Barker, Gareth R.I. (Cold Spring Harbor Laboratory Press, 2009)
Object-in-place memory, which relies on the formation of associations between an object and the place in which it was encountered, depends upon a neural circuit comprising the perirhinal (PRH) and medial prefrontal (mPFC) cortices. This study examined the contribution of muscarinic cholinergic neurotransmission within this circuit to such object-in-place associative memory. Intracerebral administration of scopolamine in the PRH or mPFC impaired memory acquisition, but not retrieval and importantly we showed that unilateral blockade of muscarinic receptors simultaneously in both regions in opposite hemispheres, significantly impaired performance. Thus, object-in-place associative memory depends upon cholinergic modulation of neurones within the PRH-PFC circuit.